Public Trust in Regional Tax Management in Sinjai Regency - Tahir, Supratman; Haning, Mohammad Thahir; Nara, Nurdin; Haris, Abd. (KnE Social Sciences, 2025)
This study examines public trust in regional tax management in Sinjai Regency, focusing on how institutional performance, communication, transparency, and fairness influence citizens’ trust in local tax authorities. Using qualitative research methods, including in-depth interviews with local residents and tax administrators, the study reveals key factors that shape perceptions of tax management. Findings indicate that while transparency and procedural fairness are central to fostering trust, inefficiencies in administrative processes, lack of effective communication, and perceived institutional bias significantly undermine trust in the system. Respondents highlighted frustrations with slow, bureaucratic procedures, insufficient outreach, and the unequal treatment of taxpayers, particularly in rural contexts where informal networks play a crucial role in mediating interactions with tax authorities. Additionally, the study explores the dual structure of trust, where citizens often trust local intermediaries over formal institutions. These insights address gaps in existing literature, particularly in rural and decentralized governance settings, by emphasizing the importance of communication and engagement strategies. The study concludes that improving institutional responsiveness, streamlining tax administration processes, and enhancing public outreach efforts are vital for rebuilding public trust in tax governance at the regional level.